EVALUATION OF Bacillus thuringiensis-BASED BIOINSECTICIDE ON THE PRESENCE OF ARTHROPODS IN VEGETATIVE PHASE OF CARROT - Novian Dwisatria; Yulia Pujiastuti; Chandra Irsan; Fitri Ramadhani (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Synthetic insecticides are still extensively used by farmers to control insect pests in carrots. The effects of excessive use of synthetic insecticides can damage agricultural ecosystems. This research aimed to examine Bacillus thuringiensis based bioinsecticide toward arthropods existence in vegetative growth phase of carrots The research was conducted in Pagar Alam City (700 m above sea level) and a relative humidity of 48–99%. The carrot plantations studied were planted in polyculture with mustard greens and sweet corn. This study used a completely randomized design (CRD) with 3 treatments and 9 replications. The treatments were bioinsecticide B. thuringiensis; synthetic insecticide (imidacloprid 200 g/l); and no-insecticide application (control). Agronomic observations were height of carrot and their number of leaves. Arthropods observations were carried out using sweep nets, pitfall traps, and direct visual observation. The results showed there was no significantly different on height of carrot plant and their number of leaves among three applications. Arthropods population in carrot plants treated with B. thuringiensis was lower than those in control carrot plants. In pitfall trap observations, the highest number of arthropod individuals obtained was belong to order Hymenoptera and had a moderate value of the Shannon-Wiener diversity index (H'). In addition, total insect population after application of B. thuringiensis observed using nets, tended to decrease from the second observation onwards. The category of insect diversity level trapped by Pitfall trap in B. thuringiensis bioinsecticide treatment was included in the medium category (H' = 1.75), while the treatment of imidacloprid (H' = 0.85) and control (H' = 0.81) was included in the low category.